Gene Polymorphism of Human Lymphotoxin Alpha in Iraqi Breast Cancer Women - Muhammed, Saadia Othman; Utba, Nawal Mohammed; Raof, Yaala Saady (Iraqi Journal of Science, 2023)
The lymphotoxin alpha is a highly polymorphic gene and any genetic variation in it may lead to an increased production of cytokine LTA thus helping tumor development and progression. The aim of this work was to investigate the association of LTA polymorphism with the risk of breast cancer among Iraqi women. The findings of this study demonstrated that the age group > 50 years old formed 52% of the breast cancer patients (P <0.001). Hardy–Weinberg equilibrium analysis revealed that genotype frequencies of most SNPs in BC patients and HC were consistent with HWE. No association was found between LTA polymorphisms and BC. Moreover, seven haplotypes were detected in BC group. However, only one of them developed significant increase; T -A -C -C -G -C –G (0.20 vs. 0.04, OR: 5.931, P = 0.015). Markedly, some SNPs were in a strong LD, while others showed weak or no LD. We can conclude that an insignificant association was found between LTA polymorphisms and breast cancer in Iraqi women.